Antitumor mechanism of MAP30 in bladder cancer T24 cells, and its potential toxic effects in mice - Shi, Zhenduo; Pang, Kun; Yang, Wen; Zhou, Jiahe; Dong, Bingzheng; Zhang, Zhiguo; Zhao, Yan; Han, Conghui; Hao, Lin (Cellular and Molecular Biology, 2020)
To investigate the antitumor mechanism of MAP30 in human bladder cell line (T24) and its potential toxic effects in mice. In this study, the biological behavior of MAP30’s influence on bladder cell was investigated to reveal the antitumor mechanism and role of MAP30 in bladder cancer. MAP30 gene sequence optimized by gene synthesis codon was inserted into the prokaryotic expression vector pET-28a to produce a large amount of target protein in Escherichia coli. The protein product was obtained after purification. Membrane hydration method was used to prepare MAP30 liposome in order to enhance its membrane permeability. The effects of MAP30 on the viability, apoptosis and migration of T24 cell were assessed using 3"‘(4,5"‘dimethyl"‘thiazol"‘2"‘yl)"‘2,5"‘diphenyl"‘2H"‘tetrazolium bromide (MTT), flow cytometric and TUNEL assays, respectively. Mice were transfected with bladder cancer cells for 48 h. The expressions of apoptotic and non-apoptotic proteins were determined using Western blotting. Changes in tumor volume and occurrence of metastasis were assessed using luciferase assay. After 7 days, liver and kidney were excised for histological examination. The levels of reactive oxygen species (ROS), malondialdehyde (MDA), and reduced glutathione (GSH), and activities of catalase and glutathione peroxidase (GPx) were determined in serum or homogenate using enzyme-linked immunosorbent assay (ELISA). The yield of MAP30 after purification was significantly increased. The results of MTT assay showed that MAP30 significantly and concentration-dependently inhibited the proliferation and migration of T24 cells (p < 0.05). The prepared liposomes had uniform hydrated particle size of 132.6 nm, with encapsulation efficiency of 78 %. The inhibitory effect of MAP30 liposome on T24 cells was significantly higher than that of MAP30, and MAP30 significantly increased the number of apoptotic cells (p < 0.05). Western blotting showed that MAP30 significantly promoted the expression of caspase 3 (p < 0.05), but did not significantly affect the expressions of bcl-2 and bax (p > 0.05). It also significantly down-regulated the expressions of NF-kB, JNK and MMP2 (p < 0.05). Tumor formation was significantly inhibited, and tumor volume reduced in bladder cancer-bearing mice after treatment with MAP30 (p < 0.05). Histological examination showed that MAP30 induced mild histological changes in the liver and kidney of mice, and significantly increased the level of MDA at day 1 (p < 0.05). It also significantly and time-dependently increased ROS, but reduced GSH levels and activities of catalase and GPx (p < 0.05). However, MAP30 had no significant effect on DNA (p > 0.05). The apoptotic effect of MAP30 in T24 cells is mediated via activation of caspase-3 signaling pathway. The protein produces mild histological changes in the liver and kidney of mice, but has no significant effect on DNA.